2009
DOI: 10.4142/jvs.2009.10.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Production of cloned sei whale (Balaenoptera borealis) embryos by interspecies somatic cell nuclear transfer using enucleated pig oocytes

Abstract: In this study, we examined the feasibility of using subzonal cell injection with electrofusion for interspecies somatic cell nuclear transfer (iSCNT) to produce sei whale embryos and to improve their developmental capacity by investigating the effect of osmolarity and macromolecules in the culture medium on the in vitro developmental capacity. Hybrid embryos produced by the electrofusion of fetal whale fibroblasts with enucleated porcine oocytes were cultured in modified porcine zygote medium-3 to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Sei whale iSCNT embryos can also be reconstructed using porcine oocytes. Porcine oocytes supported development of sei whale iSCNT embryos to the 4-cell stage, indicating that porcine oocytes can induce the nuclear reprogramming of sei whale somatic cells (Lee et al ., 2009). The high rates of developmental blockage in whale iSCNT might be due to failure in timely activation of the whale embryonic genome.…”
Section: Whale Interspecies Somatic Cell Nuclear Transfermentioning
confidence: 99%
“…Sei whale iSCNT embryos can also be reconstructed using porcine oocytes. Porcine oocytes supported development of sei whale iSCNT embryos to the 4-cell stage, indicating that porcine oocytes can induce the nuclear reprogramming of sei whale somatic cells (Lee et al ., 2009). The high rates of developmental blockage in whale iSCNT might be due to failure in timely activation of the whale embryonic genome.…”
Section: Whale Interspecies Somatic Cell Nuclear Transfermentioning
confidence: 99%
“…An in vitro developmental block has been described by several authors in iSCNT when the species of donor karyoplasts and recipient cytoplasts are far apart in their taxonomic classification. An 8-to 16-cell stage in vitro developmental block has been reported using iSCNT in the pig (Yoon et al, 2001), horse (Li et al, 2002;Sansinena et al, 2002), llama (Sansinena et al, 2003a,b), whale (Bhuiyan et al, 2009) and monkey (Song et al, 2009) when using bovine recipient cytoplasts. Although progression through the early stages of embryogenesis is regulated by maternally inherited gene products derived from the cytoplasm, the embryonic development beyond the early stages becomes dependent on embryonic gene activation at a species-specific developmental stage (Telford et al, 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Although no pregnancies were reported, this study demonstrated that the bovine oocyte is capable of supporting mitotic divisions after the introduction of a differentiated nucleus. Further iSCNT attempts using the bovine cytoplast and the karyoplasts from other species include somatic cells from pigs (Yoon et al, 2001), saolas (Bui et al, 2002), horses (Li et al, 2002;Sansinena et al, 2002;Tecirlioglu et al, 2006), bears (Ty et al, 2003), humans (Cibelli et al, 2001), desert Big Horn sheep (Williams et al, 2006), yaks (Li et al, 2007), Siberian tiger (Song et al, 2007), elands (Damiani et al, 2003;Nel-Themaat et al, 2008), red panda (Tao et al, 2009) and Sei whale (Lee et al, 2009). The first iSCNT live offspring was reported for the gaur by Lanza et al (2000) but died within the first 48 h. Using domestic sheep (Ovis aries) as recipient cytoplasts, two pregnancies were reported after iSCNT using an exotic argali (Ovis ammon) as donor karyoplasts, but both of these pregnancies were lost by 59 days of gestation (White et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used pig oocytes as recipients to reconstruct dog [ 120 , 121 ], cattle [ 120 , 122 ], mouse [ 120 , 122 ], rat [ 31 ], chicken [ 122 ], and whale iSCNT embryos [ 123 ], among others. In fact, it has been postulated that the pig oocyte could be used as a universal recipient due to its high demethylation capacity that is able to support the initiation of nucleoli formation and subsequent early embryo development in several species [ 120 ].…”
Section: Introductionmentioning
confidence: 99%